Improved Expression of SARS-CoV-2 Spike RBD Using the Insect Cell-Baculovirus System - Poodts, Joaquín (2022)
Insect cell-baculovirus expression vector system is one of the most established platforms to produce biological products, and it plays a fundamental role in the context of COVID-19 emergency, providing recombinant proteins for treatment, diagnosis, and prevention. SARS-CoV-2 infection is mediated by the interaction of the spike glycoprotein trimer via its receptor-binding domain (RBD) with the host’s cellular receptor. As RBD is required for many applications, in the context of pandemic it is important to meet the challenge of producing a high amount of recombinant RBD (rRBD). For this reason, in the present study, we developed a process based on Sf9 insect cells to improve rRBD yield. rRBD was recovered from the supernatant of infected cells and easily purified by metal ion affinity chromatography, with a yield of 82% and purity higher than 95%. Expressed under a novel chimeric promoter (polh-pSeL), the yield of rRBD after purification was 21.1 ± 3.7 mg/L, which is the highest performance described in Sf9 cell lines. Finally, rRBD was successfully used in an assay to detect specific antibodies in COVID-19 serum samples. The efficient strategy herein described has the potential to produce high-quality rRBD in Sf9 cell line for diagnostic purpose.